Obtención de un bioplástico a partir de almidón de papa (2019)
The present work of degree was based on obtaining a bioplastic having as a raw material the native potato starch. Were analyzed processes developed in different studies, grouping them into three, where they were selected by their characteristics, through a matrix of selection of weighted factors, the best process was chosen by having It counts factors such as the quality of the final material and the production time. The reinforced matrix process was the technique that was selected for obtain the bioplastic, in which the most important factor was the quality of the Final product. This process has two key blocks, the first is the starch modification, which is done to condition the starch improving its mechanical properties; the second block is the obtaining of the bioplastic where reagents are added that improve the quality and appearance of the final product. With the selected process the starch was conditioned for chemical modification by crosslinking with acetic acid.